EU integration and the introduction of State aid control in Serbia: Institutional challenges and reform prospects - Marko Milenkovic (Europa-Kolleg Hamburg, Institute for European Integration, 2016)
Serbia's EU integration has gained momentum after political change in 2000. From that point, numerous EU initiatives have been employed to facilitate the country's legal, economic and political change in order to prepare it for (potential) EU membership. The cornerstone of the relations between the country and the EU is the Stabilisation and Association Agreement, which mandates the full alignment of state aid measures to EU standards. Since 2006, subsequent governments have been working on aligning the substantive rules for the granting of state aid to the (ever-changing) EU framework, with a growing number of state aid measures and schemes being notified to and approved by the Commission for State Aid Control. However, this period was also characterised by a severe economic crisis that created the challenge for the Serbian government of aligning with the EU state aid regime, on the one hand, and facing pressure to save failing banks and companies, and prevent job losses, on the other. By examining the institutional structure of the regime's control body and the overall experiences of the first phase of the implementation of the Law on State aid, this paper draws conclusions on the major challenges and obstacles to introducing a new regulatory regime in the context of a deep economic crisis, ongoing enlargement fatigue and conflicting political legacies.
Keywords: 320; Serbia; state aid; legislative transformation; institutional independence; integration challenges; conditionality; enlargement fatigue